Neuroprotective effects of salidroside through PI3K/Akt pathway activation in Alzheimer’s disease models - Zhang B; Wang Y; Li H; Xiong R; Zhao Z; Chu X; Li Q; Sun S; Chen S (Dove Medical Press, 2016)
Bei Zhang,1,2 Ying Wang,1 Hui Li,1 Ran Xiong,1 Zongbo Zhao,1 Xingkun Chu,2 Qiongqiong Li,1 Suya Sun,1 Shengdi Chen1,2 1Department of Neurology, Institute of Neurology, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Laboratory of Neurodegenerative Diseases, The Institute of Health Sciences, Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative disorder characterized by deposits of aggregated amyloid-β (Aβ) peptide and neurofibrillary tangles in the brain parenchyma. Despite considerable research to elucidate the pathological mechanisms and identify therapeutic strategies for AD, effective treatments are still lacking. In the present study, we found that salidroside (Sal), a phenylpropanoid glycoside isolated from Rhodiola rosea L., can protect against Aβ-induced neurotoxicity in four transgenic Drosophila AD models. Both longevity and locomotor activity were improved in Sal-fed Drosophila. Sal also decreased Aβ levels and Aβ deposition in brain and ameliorated toxicity in Aβ-treated primary neuronal culture. The neuroprotective effect of Sal was associated with upregulated phosphatidylinositide 3-kinase (PI3K)/Akt signaling. Our findings identify a compound that may possess potential therapeutic benefits for AD and other forms of neurodegeneration. Keywords: Alzheimer’s disease, amyloid-β, salidroside, Drosophila, neuroprotective effect